Computer Simulations Of Void And Oxide Precipitate In Hydrogen-Annealed Silicon Wafer - Lee, Beng Gee (2004)
In this project, a computer simulation model has been developed to study the effect of annealing on the growth and dissolution of the void and oxide precipitation in Czochralski grown silicon wafer.